(untitled) (The Review of Diabetic Studies, 2024)
Introduction: The Saudi Arabian healthcare is in a radical structural change based on the framework of the Vision 2030, whereby the current structure of the system is based on departmental silos that would be integrated into a value-based care structure. The most crucial touchpoints during the clinical pathway are pharmacy, nursing, and radiology though their history has been characterized by a lack of coordination which has frequently contributed to time loss during the diagnostic process, as well as, medication errors. Following the introduction of interdisciplinary synergy in patient care by the Kingdom through the introduction of the use of "Health Clusters" and digital platforms. Objective: This systematic review will aim to assess and summarize the contributions of integrated pharmacy, nursing, and radiology services toward clinical effectiveness and patient-focused metrics within Saudi Arabia’s health care sector. Method: In accordance with the PRISMA recommendations, the systematic search was performed in PubMed, ScienceDirect, Scopus and the Saudi Digital Library to find peer-reviewed articles published in 2016-2026. Search strategies were based on the use of Boolean operators to find ways of connecting professional domains (e.g., Clinical Pharmacy) and integration concepts with the Saudi geographic context. The studies were filtered to include those that produced primary data regarding interdisciplinary collaboration between at least two of the three target departments in KSA. Conclusion: The results show that integrated service delivery has a strong positive effect on patient safety, especially with a decrease in medication and contrast-related errors of about 30-35 percent. Integration helps create a memorable patient experience, and the satisfaction score is greater as the wait time decreases, and communication between the staff is enhanced. Although digital health infrastructure is the key enabler, professional hierarchy and communication in the workplace is a challenge. The paper finds that interprofessional integration is a key to the strategic objectives of the Vision 2030, suggesting the nationwide expansion of multidisciplinary team (MDT) protocols.